2015
DOI: 10.1002/2015ja021903
|View full text |Cite
|
Sign up to set email alerts
|

Resolving daily wave 4 nonmigrating tidal winds at equatorial and midlatitudes with WINDII: DE3 and SE2

Abstract: The Wind Imaging Interferometer observed nonmigrating tidal winds from 90 to 260 km during daytime and at 99 and 250 km during the night and found that the amplitudes and phases of the daytime and nighttime extracted wave 4 for a given day were different, indicating the presence of more than one component. The objective of this study is to resolve those components. Local time versus longitude propagation plots over individual seasons revealed the diurnal eastward propagating wave number 3 (DE3), the semidiurna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Cho and Shepherd [2015] showed that the WINDII longitudinal variations of winds could be fitted with zonal wave numbers 1-4. Cho and Shepherd [2015] showed that the WINDII longitudinal variations of winds could be fitted with zonal wave numbers 1-4.…”
Section: Longitudinal Propagation Observed For Two Bright Nightsmentioning
confidence: 99%
“…Cho and Shepherd [2015] showed that the WINDII longitudinal variations of winds could be fitted with zonal wave numbers 1-4. Cho and Shepherd [2015] showed that the WINDII longitudinal variations of winds could be fitted with zonal wave numbers 1-4.…”
Section: Longitudinal Propagation Observed For Two Bright Nightsmentioning
confidence: 99%
“…WINDII provided highly accurate measurements of volume emission rates (VERs) with standard deviation estimates for the airglow VER of 1 photon cm À3 s À1 at night and 6 photons cm À3 s À1 during the day, while for the neutral wind and Doppler temperatures these are 4 m s À1 and 11 K at night and 7 m s À1 and 20 K during the day, respectively [Shepherd et al, 1993;Gault et al, 1996]. Examples of wind profiles and their errors have been presented by Cho and Shepherd [2015], who showed that the standard deviation of the O( 1 D) zonal wind varies with height with a peak of~18 m s À1 at 230 km and 7 m s À1 at 270 km, consistent with the calculated standard deviation; an example of this was given in their Figure 1d. [Walsh, 1950;Environmental Protection Agency, 1998.…”
Section: Windii Observationsmentioning
confidence: 99%
“…Various studies [ Bruinsma and Forbes , ; England et al ., ; Oberheide et al ., ; Cho and Shepherd , ] demonstrated the importance of the eastward propagating semidiurnal tide with zonal wave number 2 (SE2) for the generation of the wave 4 signatures observed in the upper atmosphere. Miyoshi et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses are based on observations of wind fields (see, e.g., Oberheide and Forbes, 2008a;Talaat and Lieberman, 2010;Lieberman et al, 2013;Cho and Shepherd, 2015) or atmospheric species emission rates or abundances (see, e.g., Oberheide and Forbes, 2008b;Oberheide et al, 2013;Nee, 2014) or the ionized atmosphere (see, e.g., England et al, 2006;Chu et al, 2009;Mukhtarov and Pancheva, 2011). Few global observations of the neutral atmosphere are available in the 100-150 km altitude range.…”
Section: Introductionmentioning
confidence: 99%